2010
DOI: 10.3109/07853890903559724
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal manifestations of inflammatory bowel disease: Epidemiology, diagnosis, and management

Abstract: Extraintestinal manifestations occur rather frequently in inflammatory bowel disease (IBD), e.g. ulcerative colitis (UC) and Crohn's disease (CD). The present paper provides an overview of the epidemiology, clinical characteristics, diagnostic process, and management of rheumatic, metabolic, dermatologic (mucocutaneous), ophthalmologic, hepatobiliary, hematologic, thromboembolic, urinary tract, pulmonary, and pancreatic extraintestinal manifestations related to IBD. Articles were identified through search of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
171
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(186 citation statements)
references
References 148 publications
3
171
1
10
Order By: Relevance
“…Up to 1/3rd of UC patients can develop extraintestinal manifestations with the skin being one of such tissues [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 1/3rd of UC patients can develop extraintestinal manifestations with the skin being one of such tissues [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is a form of inflammatory bowel disease (IBD), traditionally related to a Th2 cytokine profile mediated by 3], where immune homeostasis of the gastrointestinal tract is compromised. Up to 1/3rd of UC patients can develop extraintestinal manifestations with the skin being one of such tissues [4,5].Dendritic cells (DCs) are the most potent antigen presenting cells and determine the nature and type of immune responses [6,7]. Intestinal DCs control immune tolerance in the gastrointestinal tract [8][9][10].…”
mentioning
confidence: 99%
“…Between 20-40% of the patients with CD develop chronic inflammatory conditions located in other organs and systems, which are known as extraintestinal manifestations (EIM) of the disease (1)(2)(3)(4)(5)(6)(7)(8)(9). EIM are associated with an additional and significant morbidity and impaired quality of life (10).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies investigating the frequency of extraintestinal involvement in IBD patients, it was reported that systemic involvement was present in approximately one-third of the patients (6,7). Depending upon the areas of reporting, this rate ranges between 20% and 40% (6).…”
Section: Discussionmentioning
confidence: 99%